Comparative LC-MS/MS-based profiling of phytohormones: a unified analytical approach across diverse plant matrices - Hakeem, Muhammad K.; Rajendaran, Tamilarasan; Eldin Saeed, Esam; Mishra, Ajay K.; Hazzouri, Khaled M.; Shah, Iltaf; Amiri, Khaled M. A. (Frontiers in Plant Science, 2025)
IntroductionPhytohormones are critical regulators of plant growth, development, and stress responses. Despite advancements in analytical techniques, profiling multiple phytohormones across various plant matrices using a standardized approach remains underexplored.MethodsThis study presents a unified LC-MS/MS analytical platform, employing consistent chromatographic and mass spectrometric conditions in combination with tailored matrix-specific extraction procedures, to profile and quantify key phytohormones. This includes abscisic acid (ABA), salicylic acid (SA), gibberellic acid (GA), and indole-3-acetic acid (IAA), across five plant matrices of significant agricultural and medicinal value. The method was validated for sensitivity, reproducibility, and matrix adaptability, demonstrating robust performance in profiling phytohormones from these diverse species.ResultsThe results revealed distinct phytohormonal profiles, reflecting species-specific physiological adaptations to environmental conditions. For instance, cardamom exhibited high levels of SA and ABA, associated with stress responses in arid climates, while aloe vera showed lower phytohormone levels, indicative of its drought tolerance. Statistical analyses confirmed significant variation in hormone concentrations across the matrices, emphasizing the role of both genetic and environmental factors.DiscussionThis unified LC-MS/MS platform offers a comprehensive approach to understanding phytohormone distribution and dynamics, with implications for improving agricultural practices, crop resilience, and the development of functional foods and nutraceuticals. The findings contribute to the broader understanding of plant physiology and offer practical applications in sustainable agriculture, particularly in regions with significant agricultural and medicinal crop production.